Kemampuan Analisis Mahasiswa PGSD Terhadap Tujuan Pembelajaran Dimensi Kognitif pada Mata Kuliah Perencanaan Pembelajaran SD - Via Yustitia (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2017)
Elementary lesson plan course is a compulsory subject for students in PGSD on 5th semester. It is hoped that the students are able to create a learning design. One of the learning outcomes of this course is PGSD students are able to analyze the cognitive dimension of learning objectives based on Bloom's taxonomy revision. The problem that often arised was the students faced difficulty to identify learning objectives. This research was a qualitative research. This study aimed to determine the ability of PGSD students in analyzing the cognitive dimension of learning objectives. This study used three students class of 2014 from PGSD Universitas Adi Buana PGRI Surabaya, consisted of student who has high, medium and low capability. The instruments used were worksheets of analysis of learning objectives and guidelines for the interview. Data were collected by tests and interviews. Data analysis technique using reducing of data, presenting of data, and make inferences. The result showed that subject with high capability has been able to analyze the cognitive dimension of learning objectives well. Subject with medium and low capability have not been able to analyze the cognitive dimension of learning objectives well. It was shown from the error analysis of learning objectives and interviews. Obstacles faced by students were they did not understand the cognitive dimensions according to Bloom. The students did not understand the purpose of learning well according to the ABCD rule, and lack of precision in the analysis.